Step
*
2
1
1
1
of Lemma
simple_general_fan_theorem
1. T : Type
2. X : n:ℕ ⟶ (ℕn ⟶ T) ⟶ ℙ
3. ∀f:ℕ ⟶ T. (↓∃n:ℕ. X[n;f])
4. ∀n:ℕ. ∀s:ℕn ⟶ T.  Dec(X[n;s])
5. n : ℕ
6. s : ℕn ⟶ T
7. ∀t:T. (∃k:ℕ [(∀f:ℕ ⟶ T. ∃m:ℕk. X[(n + 1) + m;seq-append(n + 1;m;s++t;f)])])
8. K : t:T ⟶ ℕ
9. ∀t:T. ∀f:ℕ ⟶ T.  ∃m:ℕK t. X[(n + 1) + m;seq-append(n + 1;m;s++t;f)]
10. B : ℕ
11. ∀t:T. ((K t) ≤ B)
12. f : ℕ ⟶ T
13. (K (f 0)) ≤ B
14. m : ℕK (f 0)
15. X[(n + 1) + m;seq-append(n + 1;m;s++f 0;λn.(f (n + 1)))]
⊢ X[n + m + 1;seq-append(n;m + 1;s;f)]
BY
{ (NthHypEq (-1) THEN EqCD THEN Auto) }
1
.....subterm..... T:t
2:n
1. T : Type
2. X : n:ℕ ⟶ (ℕn ⟶ T) ⟶ ℙ
3. ∀f:ℕ ⟶ T. (↓∃n:ℕ. X[n;f])
4. ∀n:ℕ. ∀s:ℕn ⟶ T.  Dec(X[n;s])
5. n : ℕ
6. s : ℕn ⟶ T
7. ∀t:T. (∃k:ℕ [(∀f:ℕ ⟶ T. ∃m:ℕk. X[(n + 1) + m;seq-append(n + 1;m;s++t;f)])])
8. K : t:T ⟶ ℕ
9. ∀t:T. ∀f:ℕ ⟶ T.  ∃m:ℕK t. X[(n + 1) + m;seq-append(n + 1;m;s++t;f)]
10. B : ℕ
11. ∀t:T. ((K t) ≤ B)
12. f : ℕ ⟶ T
13. (K (f 0)) ≤ B
14. m : ℕK (f 0)
15. X[(n + 1) + m;seq-append(n + 1;m;s++f 0;λn.(f (n + 1)))]
⊢ seq-append(n;m + 1;s;f) = seq-append(n + 1;m;s++f 0;λn.(f (n + 1))) ∈ (ℕn + m + 1 ⟶ T)
Latex:
Latex:
1.  T  :  Type
2.  X  :  n:\mBbbN{}  {}\mrightarrow{}  (\mBbbN{}n  {}\mrightarrow{}  T)  {}\mrightarrow{}  \mBbbP{}
3.  \mforall{}f:\mBbbN{}  {}\mrightarrow{}  T.  (\mdownarrow{}\mexists{}n:\mBbbN{}.  X[n;f])
4.  \mforall{}n:\mBbbN{}.  \mforall{}s:\mBbbN{}n  {}\mrightarrow{}  T.    Dec(X[n;s])
5.  n  :  \mBbbN{}
6.  s  :  \mBbbN{}n  {}\mrightarrow{}  T
7.  \mforall{}t:T.  (\mexists{}k:\mBbbN{}  [(\mforall{}f:\mBbbN{}  {}\mrightarrow{}  T.  \mexists{}m:\mBbbN{}k.  X[(n  +  1)  +  m;seq-append(n  +  1;m;s++t;f)])])
8.  K  :  t:T  {}\mrightarrow{}  \mBbbN{}
9.  \mforall{}t:T.  \mforall{}f:\mBbbN{}  {}\mrightarrow{}  T.    \mexists{}m:\mBbbN{}K  t.  X[(n  +  1)  +  m;seq-append(n  +  1;m;s++t;f)]
10.  B  :  \mBbbN{}
11.  \mforall{}t:T.  ((K  t)  \mleq{}  B)
12.  f  :  \mBbbN{}  {}\mrightarrow{}  T
13.  (K  (f  0))  \mleq{}  B
14.  m  :  \mBbbN{}K  (f  0)
15.  X[(n  +  1)  +  m;seq-append(n  +  1;m;s++f  0;\mlambda{}n.(f  (n  +  1)))]
\mvdash{}  X[n  +  m  +  1;seq-append(n;m  +  1;s;f)]
By
Latex:
(NthHypEq  (-1)  THEN  EqCD  THEN  Auto)
Home
Index